If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 8x + -2 + x(-7x + -6) Multiply f * x fx = 8x + -2 + x(-7x + -6) Reorder the terms: fx = 8x + -2 + x(-6 + -7x) fx = 8x + -2 + (-6 * x + -7x * x) fx = 8x + -2 + (-6x + -7x2) Reorder the terms: fx = -2 + 8x + -6x + -7x2 Combine like terms: 8x + -6x = 2x fx = -2 + 2x + -7x2 Solving fx = -2 + 2x + -7x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -2x-1 + 2 + -7x Simplifying f = -2x-1 + 2 + -7x Reorder the terms: f = 2 + -2x-1 + -7x
| 5y-9=48+2y | | 5-4-2n=-35 | | 2(x+4)-3(x-3)=0 | | 9x+4=14-8x | | 8=3x+3x-10 | | 2(3x+7)=-26 | | X-1+x=21 | | 3(cotx-1)=0 | | 11=-22-3x | | -4c+5=13 | | 700=4.5+9.0 | | 8x^2+10x=42 | | -1-4x=47 | | 68=a+5+a-12 | | 5(3x+2)=6(x+2) | | 2(x+4)+3(X-1)=15 | | 5(3x+12)=6(x+2) | | 3x(3x-8)-8=9x(x-3)+4 | | 5(x+25)=140-6x | | y=x+4-4 | | 2x+4y+6z=86.8 | | (x-3)=5(3x-8) | | -3+11=14x-2-13x | | 2-8x+6=70 | | -7x+9=-54 | | 2s+4=4 | | 4*x*x*x=20 | | 2/3•3.14•6 | | 16a^3-24a^2-39a+15=0 | | 3(x+7)-21= | | 20=1.4+0 | | X+1=81 |